A Case Study of Middle Grades Leadership in a Conversion Charter School. (March 2015) - Bickmore, Dana L.; Dowell, Margaret-Mary Sulentic
This 3-year case study examined middle grades principal leadership in a takeover charter school. The researcher analyzed principal and teacher interviews, field notes, and documents in relationship to a middle grades model of principal leadership. Results suggest the principals' limited experience, organizational factors unique to takeover charter schools, an emphasis on student test scores, and a personal educational philosophy of teacher autonomy, precluded the advocacy and implementation of elements of the middle grades principal leadership model.